Forensic Evaluation of Various Osteometric Parameters of Human Mandible in both Sexes - Priyamvada Kurveti1 , Gyanendra Kumar2, Dheeraj Singh Verma3, JayanthiYadav4, B. P. Dubey5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Identification of sex could be made on differences in the size and shape of the morphological markers i.e. shapes of chin, size of condyles etc. Morphological traits are more subjective and sex determination depends on experience of the investigator. So, visual methods of sexing mandible are likely to be inaccurate when performed by an inexperienced worker and sometimes produce misleading results. Hence, metric analyses are found to of superior value owing to their objectivity, accuracy, reproducibility and lower incidence of inter and intra observer errors as compared to that of descriptive traits.The focus on present study is to use morpho-metric analytical method to evaluate the ability of selected parameters to determine sex in forensic sample.Aims and Objectives: To study the various osteometric parameters of human mandible and evaluate their utility in sex determinationMaterial and Method: Some measurements of the 200 mandibles were taken using sliding calliper and mandibulometer and statistically analysed.Findings: On statistical analysis, it is found that height of the symphysis menti, bigonial width, shows a higher index of sexual dimorphism. Hence, these can be used for determination of sex. Other parameters such as bicondylar width, mandibular angle are found to be statistically insignificant in this study.Conclusion : When the findings of present study were compared with those of past investigators, marked variations in the various osteometric parameters of mandible was noticed, which differed all over the world as well as in different regions of India. Hence, it is suggested, not to apply the findings of study of one region over the samples of other region, to avoid fallacies.